SARS-CoV-2 vaccination patterns in a private hematology and internal medicine outpatient clinic - Elizabeth García-Villaseñor; Lorena Bojalil-Álvarez; Oscar A Reyes-Cisneros; José A Fernández-Gutiérrez; Daniela Sánchez-Bonilla; Max Robles-Nasta; Moisés Manuel Gallardo-Pérez; Iván Murrieta-Álvarez; Guillermo J Ruiz-Delgado; Guillermo J Ruiz-Argüelles (Instituto Nacional de Salud Pública, 2022)
Objective. Determine the proportion of vaccinated patients in a private hematology and internal medicine outpatient clinic and potential factors in adherence in at-risk patients (due to onco-hematological diseases). Materials and methods. This is a cross-sectional study of outpatients from a private clinic. We applied a non-validated instrument to all patients attending the outpatient clinic from May to October 2021. According to the primary diagnosis, we classified patients into onco-hematological and non-onco-hematological patients. Since national authorities exclusively executed and planned the rollout of vaccines, the order and eligibility defined by authorities of vaccination was considered when conducting the analysis and patients were classified according to the their corresponding group. Results. 397 participants were accrued, 269 (68%) had an onco-hematological condition. In the whole group, 73 (18.3%) had a history of infection. Vaccination history was present in 286 persons (72%); 82% had two doses. In the subset of 269 persons with an onco-hematological condition, 191 (71%) were vaccinated, whereas 95 participants with non-hematological conditions (73%) had received the vaccine. Vaccination status was associated with age (OR 1.07, 95%CI: 1.03,1.10, p<0.0001) and body mass index (OR 1.11, 95%CI: 1.04,1.17, p<0.0001). Conclusions. According to our study, vaccination adherence at our center is significantly different from the nationwide proportion of vaccines.